Model Kurikulum Pendidikan Jihad di Ma’had Aly Ar-Rahman Qur’anic College (AQC) Bogor - Haris Renaldi; Hidayati Hidayati (Edukasi Islami : Jurnal Pendidikan Islam, 2021)
This study focuses on discussing the model of jihad education curriculum in Islamic education. This research was conducted at the student boarding school of Ar-Rahman Qur'anic College (AQC) Bogor with the aim of knowing the model of the jihad education curriculum applied at the institution. This jihad education is one of the educations taught at AQC Bogor, so that students understand jihad comprehensively according to the basis of Islam, are the Qur'an and Hadith. In this study used is qualitative research with the type of research is field research, that research conducted by means of observation, documentation and interviews. This study concludes that jihad education at Ma'had Aly Ar-Rahman Qur'anic College Bogor makes the students have scientific insight and correct understanding of jihad in accordance with the Qur'an and Sunnah, have pure faith, consistent worship, civilized and morals, and become a cadre of mujahid da'wah. Jihad education curriculum materials at AQC consist of monotheism, sincerity, adab and morals, worship and life skills. The methods of jihad education applied at AQC are the lecture method, memorization, tarhib and targhib, and prayer. Meanwhile, there are four evaluations that can be done in the jihad education curriculum, they are formative evaluation, summative evaluation, moral evaluation, and evaluation with time.